Development of Indonesian Language Curriculum Based on Islamic Values in Responding to the Challenges of Digital Literacy - Tawakkal, M. Iqbal; Sahri (Institut Darul Falah Bandung Barat, 2025)
This research aims to develop an Islamic values-based Indonesian curriculum in response to the challenges of digital literacy at Al Fattah Pungpungan Islamic High School. The curriculum is designed to enhance students' language skills, encompassing reading, writing, listening, and speaking, while instilling Islamic values that are relevant to the digital age. Through the Research and Development (R&D) approach, this research produces a curriculum that integrates digital literacy and Islamic values into the learning process. The research findings indicate that the developed curriculum is effective in enhancing students' digital literacy skills, fostering Islamic character in digital communication, and improving overall language proficiency. Limited trials and wide implementation in grades X and XI have demonstrated that students are more active, critical, and responsible in their digital interactions. This curriculum also has a positive impact on improving writing and speaking skills that reflect Islamic manners. The curriculum based on Islamic values at MA Al Fattah Pungpungan has successfully enhanced digital literacy, Islamic character, and the quality of learning, making it suitable for replication in other madrasahs with contextual adjustments.